Pemanfaatan Tanaman Daun Gatal di Arso XIV - Eva Susanty Simaremare; Rani Dewi Pratiwi; Elsye Gunawan (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2019)
Wulukubun Arso XIV, District Skanto Kerom regency is overgrown with stingging nettle leaves that are useful as traditional medicine as pain relief, reduce fatigue, and reduce stiffness. Stingging nettle leaves are found in the village but they are only allowed to dry, wilted, dead, even thrown away. On the other hand the value of this leaf is higher if they are developed as pharmaceutical products. The purpose of this activity was to carry out a program to empower, strengthen community participation in swamedication and optimization the potency of stingging nettle leaf to raise the health and economics of Wulukubun Arso XIV people as topical ointment. This activity was taked out by the preparation method, established cooperation with partners, related institutions, activities of the activity day in the village, evaluation, report, and publication. The results showed 7.4% of participants have followed the same activity. As many as 88.9% of participants got new information from this activity and 70.4% committed to assist others in disseminating the information from this activity